Beethoven's "Orpheus" Concerto: The Fourth Piano Concerto in its Cultural Context - Jander, Owen (Hillsdale, NY Pendragon, 2011)
Beethoven composed his Fourth Piano Concerto in Vienna in the years 1803-06. In that period there was an unusually keen interest in the Orpheus legend; and so it is not surprising to learn that all three movements ... were undeclaredly or better described, secretly based on that famous story.So begins Owen Jander's Beethoven's "Orpheus" Concerto: The Fourth Piano Concerto in its Cultural Context. In this fascinating and controversial book, the author maintains echoing the interpretation first suggested by Adolph Berhard Marx in 1859 that the three movements are based on the Classical versions of the Orpheus legend by Virgil and Ovid. Jander tells us the full story from the opening phrase of the first movement to the last measure of the finale of how the Orpheus legend informs every note of Beethoven's music.
Keywords: Orpheus; 19th Century (1801-1900); Concerto; Piano; Musical analysis; Cuckoo; Mythology; Vienna (Austria)